Programming the World - Beigl, Michael; Michahelles, Florian; Tokuda, Hide; Hodges, Steve (Computer (Long Beach, Calif.), 2017)
Computing evolution has brought about multiple paradigm shifts in how we use technologies. In the living laboratory that is modern life, our ability to design and control the computers and computing power of the future will require an ability to program systems and applications in situ and in vivo.